Developing Intercultural Identity on a Sojourn Abroad: A Case Study - Sobkowiak, Paweł (Studia Anglica Posnaniensia, 2021)
This article reports on a longitudinal case study and gives first-hand accounts of the lived experiences of five Erasmus+ students from Turkey during their sojourn at a university in Poland and its impact on the students’ individual identities. The research aimed to investigate students’ learning experience at the host institution and intercultural adaptation, focusing on the transformative outcomes that the sojourn brought about in them. The framework used as a theoretical basis for the study was Kim’s integrative theory of communication and cross-cultural adaptation. The theory claims that cultural adjustment is a function of an individual’s development of social and personal communication competence in their respective environments. As a result of frequent meaningful interactions with cultural others, through meeting and overcoming multiple intercultural challenges, people are likely to develop intercultural personhood, going through three consecutive stages, i.e., stress-adaptation-growth (Kim 2008). The study outcomes show sojourning abroad as a rather positively valenced experience, contributing to participants’ gaining knowledge about diverse cultures, the skills to cope with diversity and an increased willingness to interact with people from different ethnic backgrounds. The data revealed that the participants underwent, to a moderate degree, a cultural identity shift toward becoming more mindful, open-minded, self-other oriented, and inclusive toward diversity.